2022
DOI: 10.7759/cureus.25662
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic Bile Duct Injury Caused by Blunt Abdomen Trauma: A Case Report

Abstract: Traumatic injuries to the extra-hepatic biliary tract are uncommon and may be suspected intraoperatively by the presence of bile-stained fluid in the subhepatic area. We present a case of injury to the common bile duct in a polytrauma patient. The initial CT scan did not suggest biliary injury. However, intraoperatively, bile-stained fluid in the subhepatic space raised suspicion of bile duct injury. This was confirmed postoperatively in the development of a biliary fistula after the primary laparotomy. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Ghosh et al [ 10 ] recently reported a case of extrahepatic duct injury after blunt trauma that failed to respond to NOM after 2 days in the ICU due to peritonitis. The patient underwent laparotomy and the injury to the main bile duct was not identified during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh et al [ 10 ] recently reported a case of extrahepatic duct injury after blunt trauma that failed to respond to NOM after 2 days in the ICU due to peritonitis. The patient underwent laparotomy and the injury to the main bile duct was not identified during the procedure.…”
Section: Discussionmentioning
confidence: 99%